ANALISIS RASIO PROFITABILITAS TERHADAP KINERJA KEUANGAN PT INDOFOOD CBP SUKSES MAKMUR TBK. PERIODE 2019-2023 - Aulia Fasha Julianti; Adinda Nada Khalisha (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
This study aims to measure the financial performance of Indofood CBP Success Wealth Tbk using profitability ratio. In this study, we used three profitability ratios namely, Return On Asset (ROA), and Return on Equity (ROE), and Net Profit Margin (NPM) to assess the financial performance of Indofood CBP Sukses Makmur Tbk. during the period 2019-2023 using quantitative descriptive research. Overall PT Indofood CBP Success Makmur Tbk. showed fairly good performance in terms of efficiency of use of assets and equity compared to its competitors.